A real difference or creative summary measures? [4] (multiple letters) - Gilles, Jerry M.; Jacques, Elvire; Diro, Makbib; Burkett, Gene; Chan, Louis Y.; Çelik, Husnu (Elsevier Inc., 2004)
[Abstract Not Available]
Keywords: gonadorelin; gonadorelin derivative; misoprostol; prostaglandin; prostaglandin E1; vasopressin; bleeding; blood transfusion; clinical research; clinical trial; drug activity; drug effect; drug indication; ductus arteriosus; follicular phase; human; hypovolemia; letter; luteal phase; menstrual cycle; menstruation; myomectomy; myometrium; operation duration; preoperative care; priority journal; sample size; uterine cervix dilatation; vascular patency; vascular tissue